42 The prevalence of takotsubo cardiomyopathy in patients admitted to the intensive care unit. (16th October 2019) - Carton, M; Donnelly, M; Fahy, A; Coughlan, JJ; Loo, B; Moore, D
Abstract : Background: Takotsubo Cardiomyopathy (TCM) is an acute cardiac condition independent of epicardial coronary obstruction, mimicking an acute coronary syndrome and is characterised by acute heart failure with reversible ventricular wall motion abnormalities. It is associated with a wide variety of physical, psychological and emotional stressors. Patients admitted to the intensive care unit (ICU) are exposed to significant stressors and so may be at an increased risk of developing TCM. There are limited data outlining the prevalence of TCM in the ICU. As a result the quoted figures vary considerably in the literature, with reported prevalences ranging from 0.9 to 28%. In this study, we sought to define the prevalence of regional wall motion abnormalities consistent with TCM in patients admitted to the ICU in our centre. Methods: A retrospective cross sectional study was performed in our centre. This included all patients admitted to the Intensive Care Unit in Tallaght University Hospital over a 13 month period: January 2018 - February 2019. Baseline, demographic, clinical, laboratory and technical data was collected for all patients using our IT system and a database was formed. An independent cardiologist retrospectively reviewed all echocardiograms performed within the study period. Results: There were 358 patients admitted to the ICU during the study period. The mean age was 59.8±17 years, over half of the patients (55%) were male. One hundred and fifteen patients (32%) had a reported transthoracic echocardiogram on our system. Of these echocardiograms 58 (50%) were reported as completely normal and 27 (23%) had minor abnormalities, including concentric left ventricular (LV) hypertrophy, n=12; hyper-dynamic LV function, n=6; diastolic dysfunction, n=9. Significant abnormalities were identified in 25 cases (22%). These included moderate-severe reductions in LV function, n=9; and LV hypokinesia/akinesia/dyskinesia, n=16. Of the 16 patients with LV hypokinesia/akinesia/dyskinesia, 10 had new regional wall motion abnormalities (RWMA) potentially consistent with TCM. Indications for ICU admission within this group included: urosepsis, respiratory sepsis, ischemic bowel, acute pancreatitis and seizures. Only 3 of these patients (0.84% of total ICU admissions) had a repeat echocardiogram confirming recovery of RWMA consistent with TCM. The majority of these patients had no follow up echocardiogram (N=7). Of note, 50% of this cohort did not survive to discharge. Of the 10 patients with potential or confirmed TCM, the ICU length of stay was longer when compared to all other ICU admissions for the same period (Median 17.36 days, IQR 15.83 vs 3.79 days, IQR 7.13, p=0.00694). The rate of survival to hospital discharge rate was numerically lower in this cohort but this did not reach statistical significance (50% vs 68%, p=0.169). Conclusion: Echocardiography was performed on one-third of patients admitted to the ICU. Of these echocardiograms, 73% of studies were reported as normal or showing only minor abnormalities. Wall motion abnormalities potentially consistent with TCM were identified in 3% of all patients admitted to the intensive care unit. Two-thirds of patients with new or indeterminate RWMA in the ICU did not receive follow up investigations. As such, RWMA consistent with TCM were confirmed in only 3 patients, resulting in a prevalence of 0.84% in our study population. A more standardised approach may help determine the true prevalence of this condition.